Genetic signature to provide robust risk assessment of psoriatic arthritis development in psoriasis patients - Matthew T. Patrick (Nature Portfolio, 2018)
Approximately 30% of psoriasis patients develop psoriatic arthritis (PsA) and early diagnosis is crucial for the management of PsA. Here, Patrick et al. develop a computational pipeline involving statistical and machine-learning methods that can assess the risk of progression to PsA based on genetic markers.